(untitled) (Research, Society and Development, 2024)
Lifestyle plays a crucial role in determining certain mental and medical conditions. The aim of this article is to present a protocol to evaluate, based on scientific evidence from the literature, the association between medical students’ lifestyle and mental illness during their undergraduate studies. Review method: the protocol for this study was developed in accordance with the PRISMA guidelines for systematic review protocols and will be registered in the PROSPERO database. The search will be conducted in the following databases: Scopus, EMBASE, SciELO, and MEDLINE via PubMed. Grey literature will also be included in the search. Two independent and blind reviewers will participate in the selection of studies. The quality of the evidence will be assessed using the instruments proposed by the Joanna Briggs Institute. The quantitative analysis of the included studies will be represented by a meta-analysis; however, if this is not feasible, the data will be presented through a descriptive analysis. The systematic review and meta-analysis of studies on etiology and risk can provide valuable information for health professionals and policymakers, clarifying disease risk factors and identifying areas where other factors, besides direct interventions with therapy and treatment, can influence health outcomes. Final considerations: Identifying the relationship between lifestyle and triggering factors of mental illness is essential to guide the implementation and development of alternatives to improve the lifestyle of students.